Application of Intravenous Lidocaine in Obese Patients Undergoing Painless Colonoscopy: A Prospective, Randomized, Double-Blind, Controlled Study - Li X; Lv X; Jiang Z; Nie X; Wang X; Li T; Zhang L; Liu S (Dove Medical Press, 2020)
Xiaoxiao Li,1,* Xueli Lv,1,* Zhenfei Jiang,1 Xinrui Nie,1 Xinghe Wang,1 Tong Li,1 Lianyi Zhang,2 Su Liu1,2 1Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Su Liu Department of AnesthesiologyThe Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu 221000, People’s Republic of ChinaTel +86 18118309692Fax +86 516-8346-9496Email liusu112277@gmail.comObjective: Propofol for procedural sedation and analgesia (PSA) for colonoscopy can result in a high prevalence of severe respiratory depression. Studies have shown that intravenous (IV) infusion of lidocaine can reduce propofol requirements significantly and increase the ventilatory response to carbon dioxide in humans. We tested the hypothesis that IV lidocaine could improve propofol-induced respiratory depression in obese patients during colonoscopy.Methods: Ninety obese patients scheduled for painless colonoscopy were randomized to receive lidocaine (1.5 mg/kg, then 2 mg/kg/h, IV) or the same volume of 0.9% saline. Intraoperative sedation was provided by propofol. The primary outcome was the number of oxygen-desaturation episodes. Secondary outcomes were: the number of apnea episodes; total propofol consumption; time to the first hypoxia episode; time to consciousness loss; intraoperative hemodynamic parameters; awakening time; adverse events; duration of post-anesthesia care unit (PACU) stay; satisfaction of endoscopists and patients.Results: Demographic characteristics between the two groups were comparable. The number of oxygen-desaturation episodes in group L (1.49± 1.12) decreased by 0.622 (P=0.018) compared with that in group N (2.11± 1.32), and the number of apnea episodes in group L decreased by 0.533 (P< 0.001). Kaplan–Meier curves showed that the median time to the first hypoxia episode was longer in group L (86.78 s) than that in group N (63.83 s) (Log rank P=0.0008). The total propofol consumption, awakening time, and duration of PACU stay were reduced in group L. There was no significant difference in the prevalence of adverse events (P> 0.05 for all). Satisfaction scores for endoscopists and patients in group L were higher than that in group N (P< 0.001).Conclusion: Intravenous infusion of lidocaine could significantly reduce the number of oxygen-desaturation and apnea episodes in obese patients during painless colonoscopy. This method is worthy of clinical promotion.Clinical Trials Registration: ChiCTR2000028937.Keywords: lidocaine, propofol, obese patients, colonoscopy